Epidermal Growth Factor Downregulates Carbon Anhydrase III (CAIII) in Colon Cancer - Derya Okuyan (Current Issues in Molecular Biology)
Colorectal cancer (CRC) is the second leading cause of cancer-related death in the world. Dysregulations in the EGF signaling pathway have been associated with colon cancer. Some members of the carbonic anhydrase family serve as biomarkers in cancer. Carbonic anhydrase III (CAIII), a member of this family, shows different activities than the other members of its family and has been associated with cancer. However, there are no studies on the effective regulation of EGF. In this study, we investigated the EGF-influenced regulation of CAIII in the HT29, SW480, and HUVEC cell lines and showed that CAIII regulation decreased with the effect of EGF. We aimed to investigate the EGF-affected mRNA and protein regulation of the CAIII gene in HT29, SW480, and HUVEC cell lines. For this purpose, we determined time-dependent CAIII mRNA and protein expression by applying EGF to HT29, SW480, and HUVEC cells. Time-dependent EGF-induced mRNA and protein level regulation of the CAIII gene decreased in the HT29, SW480, and HUVEC cell lines. EGF regulates the motility, adhesion, and metastasis of cancer cells. CAIII prevents cells from metastasizing through cell acidification. Therefore, our findings explained why the EGF-effective regulation of CAIII decreased. We suggest that the CAIII gene is promising as a targeted therapy due to the decrease in EGF-effected CAIII gene regulation in colon carcinoma.